2018
DOI: 10.1007/s11255-018-1809-x
|View full text |Cite
|
Sign up to set email alerts
|

Visual internal urethrotomy for management of urethral strictures in boys: a comparison of short-term outcome of holmium laser versus cold knife

Abstract: Laser VIU has a higher success rate than cold knife VIU for urethral strictures ≤ 1.5 cm in children with significantly higher Q. Both are easy to perform, low invasive and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…After applying selection criteria, 22 articles reporting data on 682 patients were included into analyses. Treatment approaches varied across the studies with seven articles reporting on urethrotomy or dilation (410), 11 articles reporting on urethroplasty (1121), and four articles reporting on both techniques in comparative analyses (2225). A summary of all articles considered for this review is depicted in Tables 1–3.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After applying selection criteria, 22 articles reporting data on 682 patients were included into analyses. Treatment approaches varied across the studies with seven articles reporting on urethrotomy or dilation (410), 11 articles reporting on urethroplasty (1121), and four articles reporting on both techniques in comparative analyses (2225). A summary of all articles considered for this review is depicted in Tables 1–3.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, seven studies reported on outcomes after endoscopic treatment (urethrotomy or dilation) (410) and four studies reported on comparative outcomes following endoscopic treatment vs. urethroplasty (2225) (Tables 2, 3). Of note, only two articles performed a (partially) prospective data collection (4, 10) and thus, the level of evidence was low.…”
Section: Endoscopic Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…No significant difference was found between the two groups in the first publications (2). However, as a result of the advances in laser technology, increased experience and more studies conducted, significant differences are observed between the two groups in recent publications (3,4).…”
Section: Introductionmentioning
confidence: 99%